Political Dynamics in Education Policy in Indonesia: A Systematic Literature Review - Ruth Sriana Umbase; Yohanes Bery Mokalu; Dhea Jessica Sendiang; Herman Philips Dolonseda; Rofinus Banunaek (SOSCIED, 2026)
This study examines the political dynamics shaping education policy in Indonesia through a systematic literature review (SLR). While education policy is often framed as a technical and rational process, increasing evidence suggests that political interests, power relations, and governance structures play a decisive role in policy formulation and implementation. Using the PRISMA framework, this study analyzes peer-reviewed articles published between 2015 and 2025. The findings reveal that education policy in Indonesia is strongly influenced by elite actors, decentralization politics, institutional fragmentation, and ideological contestation. The review further demonstrates that decentralization reforms have produced both opportunities for local participation and challenges related to policy inconsistency and unequal implementation across regions. This study proposes a Political–Policy Interaction Model that conceptualizes policy processes as dynamic interactions between political forces and governance structures. The findings contribute to Public Policy Analysis by integrating political economy and governance perspectives into education policy research, particularly in developing countries.